2019
DOI: 10.1038/s42255-019-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial TGF-β signalling drives vascular inflammation and atherosclerosis

Abstract: Atherosclerosis is a progressive vascular disease triggered by interplay between abnormal shear stress and endothelial lipid retention. A combination of these and, potentially, other factors leads to a chronic inflammatory response in the vessel wall, which is thought to be responsible for disease progression characterized by a buildup of atherosclerotic plaques. Yet molecular events responsible for maintenance of plaque inflammation and plaque growth have not been fully defined. Here we show that endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
193
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(200 citation statements)
references
References 44 publications
7
193
0
Order By: Relevance
“…24,25 within the vessel wall. Importantly, elevated TGF-β1 levels and altered downstream signalling have been implicated in the etiology of atherosclerosis 26 , vessel restenosis 27 and in the development of the neointima 28 . Genome-wide association studies have also identified chromosome 14q32 as a locus for a hitherto uncharacterized gene called HHIPL1 (Hedgehog interacting protein-like 1) 29 which encodes a sequence homolog of an antagonist of hedgehog signalling that is secreted as a pro-atherogenic protein to regulate lesion formation 30 .…”
Section: Tgf-β1 Is Released By Both Inflammatory Cells and Vascular Cmentioning
confidence: 99%
“…24,25 within the vessel wall. Importantly, elevated TGF-β1 levels and altered downstream signalling have been implicated in the etiology of atherosclerosis 26 , vessel restenosis 27 and in the development of the neointima 28 . Genome-wide association studies have also identified chromosome 14q32 as a locus for a hitherto uncharacterized gene called HHIPL1 (Hedgehog interacting protein-like 1) 29 which encodes a sequence homolog of an antagonist of hedgehog signalling that is secreted as a pro-atherogenic protein to regulate lesion formation 30 .…”
Section: Tgf-β1 Is Released By Both Inflammatory Cells and Vascular Cmentioning
confidence: 99%
“…Then, we explored why material topography mediated the adhesion of monocytes to ECs. As it was demonstrated that both ICAM-1 and VCAM-1 were closely related to the interplay of ECs and monocytes, 34,35 the endothelial expression of ICAM-1 and VCAM-1 was tested in ECs cultured on PDMS substrates with different dimensions. The gene expression of ICAM-1 and VCAM-1 was performed by RT-qPCR.…”
Section: The Adhesion Of Monocytes To Huvecs Is Affected By Wrinkledmentioning
confidence: 99%
“…Recruitment of lentiviral transduced leukocytes in the sterile peritonitis model. In many murine disease models recruitment of leukocyte subpopulations of interest to the site of inflammation is a critical readout [21][22][23] . Therefore, we induced a sterile peritonitis 24 weeks following HSC transfer.…”
Section: Functional Assessment Of the Bicistronic Lentiviral Construcmentioning
confidence: 99%